2012
DOI: 10.1007/s10725-012-9771-6
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza improved growth performance in Macadamia tetraphylla L. grown under water deficit stress involves soluble sugar and proline accumulation

Abstract: Water deficit limits plant growth and yield. Arbuscular mycorrhizal (AM) symbiosis is viewed as one of the several methods to improve growth under water deficit. The present study investigated the growth performance in relation to water deficit in two cultivars (''H2'' and ''660'') of AM treated macadamia (Macadamia tetraphylla L.) plants. AM treatment significantly improved the growth in macadamia plants that have been subjected to water deficit (7 % soil water content) for 14 days. Leaf water content (LWC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 46 publications
5
63
1
Order By: Relevance
“…The colonization of roots by AM fungi in various plant species induces proline accumulation when water is limiting Azcón et al 1996;Goiochea et al 1998;Yooyongwech et al 2013). The enhanced accumulation of proline in these studies was linked to AM-induced drought resistance with proline acting as osmoprotectant.…”
Section: Role Of Metabolic Changes In Osmoregulationmentioning
confidence: 95%
See 2 more Smart Citations
“…The colonization of roots by AM fungi in various plant species induces proline accumulation when water is limiting Azcón et al 1996;Goiochea et al 1998;Yooyongwech et al 2013). The enhanced accumulation of proline in these studies was linked to AM-induced drought resistance with proline acting as osmoprotectant.…”
Section: Role Of Metabolic Changes In Osmoregulationmentioning
confidence: 95%
“…Recent reports have indicated that AM symbiosis under drought conditions enhances the photochemical efficiency of photosystem II, given by Fv/Fm, assessed by chlorophyll fluorescence in rice plants (Ruiz-Sánchez et al 2011) and in woody tree nut species (Yooyongwech et al 2013). Such results indicate the improved performance of the photosynthetic machinery and the absence of photoinhibition when mycorrhizal plants were exposed to water deficit.…”
Section: Aboveground Processes Affecting Plant-water Relationsmentioning
confidence: 96%
See 1 more Smart Citation
“…5A). In the presence of AM symbiosis and upon WS conditions, the content of Pro was reported to be either higher (Ruíz-Sánchez et al, 2011;Abbaspour et al, 2012;Yooyongwech et al, 2013) or lower Bhosale and Shinde, 2011;Zou et al, 2013;Wang et al, 2014;Hazzoumi et al, 2015) than in control plants. Our results, showing a higher content of Pro in AM+ plants during WS with respect to control plants, could suggest a better resistance of colonized plants to WS.…”
Section: Pro and Hydrogen Peroxide Contents And Superoxide Dismutase mentioning
confidence: 98%
“…In the case of micropropagated hazelnut plants, colonization with AMF improves growth rather than survival (Mirabelli et al 2009). Drought tolerance of Macadamias improves when mycorrhized (Yooyongwech et al 2013). Similarly, we could not find any information concerning the effect of PGPR on the quality of O. europaea fruits; actually, the only report concerns the rooting induction of some auxin-producing bacteria on olive cuttings (Montero-Calasanz et al 2013).…”
Section: 3mentioning
confidence: 65%